FRACTIONAL CRYSTALLIZATION OF HYDROUS BASALTIC "ARC-TYPE" MAGMAS AND THE FORMATION OF AMPHIBOLE-BEARING GABBROIC CUMULATES - Claeson D.T.; Meurer W.P. (My University, 2004)
The Rymmen and Eriksberg gabbros preserve the crystallization products of hydrous basaltic liquids, ranging from anorthosite and troctolite to highly fractionated oxide gabbro, diorite, and leucotonalite. The high initial water content of the liquids that filled the magma chambers (1.5–3wt%) allowed amphibole to saturate as an interstitial mineral even in the earliest formed cumulates. The increasing water content of the system helped to produce a thick sequence of cumulates with anorthitic plagioclase (An87–92). The growth of interstitial amphibole caused much more interstitial liquid to be incorporated into the cumulates than might be expected for dryer basaltic systems, producing a very imperfect fractional crystallization process. Comparisons of models of the trace-element evolution of the two intrusions reveal that the overall enrichments of some elements are adequately predicted by a perfect fractional crystallization model but all agree better with an imperfect fractional crystallization model. This reflects the change in the bulk distribution coefficients of the solid assemblage upon amphibole saturation, with the retention of elements compatible in amphibole in the crystal pile and the loss of elements incompatible in amphibole from it. These results stress the importance of understanding the physical, as well as the chemical processes involved in fractional crystallization and in particular the role of postcumulus processes.